Cutting Balloon Angioplasty in the Treatment of Short Infrapopliteal Bifurcation Disease. (August 2015) - Iezzi, Roberto; Posa, Alessandro; Santoro, Marco; Nestola, Massimiliano; Contegiacomo, Andrea; Tinelli, Giovanni; Paolini, Alessandra; Flex, Andrea; Pitocco, Dario; Snider, Francesco; Bonomo, Lorenzo
Purpose: To evaluate the safety, feasibility, and effectiveness of cutting balloon angioplasty in the management of infrapopliteal bifurcation disease.Methods: Between November 2010 and March 2013, 23 patients (mean age 69.6±9.01 years, range 56–89; 16 men) suffering from critical limb ischemia were treated using cutting balloon angioplasty (single cutting balloon, T-shaped double cutting balloon, or double kissing cutting balloon technique) for 47 infrapopliteal artery bifurcation lesions (16 popliteal bifurcation and 9 tibioperoneal bifurcation) in 25 limbs. Follow-up consisted of clinical examination and duplex ultrasonography at 1 month and every 3 months thereafter.Results: All treatments were technically successful. No 30-day death or adverse events needing treatment were registered. No flow-limiting dissection was observed, so no stent implantation was necessary. The mean postprocedure minimum lumen diameter and acute gain were 0.28±0.04 and 0.20±0.06 cm, respectively, with a residual stenosis of 0.04±0.02 cm. Primary and secondary patency rates were estimated as 89.3% and 93.5% at 6 months and 77.7% and 88.8% at 12 months, respectively; 1-year primary and secondary patency rates of the treated bifurcation were 74.2% and 87.0%, respectively. The survival rate estimated by Kaplan-Meier analysis was 82.5% at 1 year.Conclusion: Cutting balloon angioplasty seems to be a safe and effective tool in the routine treatment of short/ostial infrapopliteal bifurcation lesions, avoiding procedure-related complications, overcoming the limitations of conventional angioplasty, and improving the outcome of catheter-based therapy.